Assessing Efficiency of Paddy Farming in Deli Serdang Regency, North Sumatra, Indonesia - Kabeakan, Nana Trisna Mei Br; Purba, Khairul Fahmi; Intan, Dian Retno; Lubis, Wildani; Vionika, Cahya (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The use of agricultural input is significant for farm management. It would relate to productivity and efficiency. The problem is that the paddy farmers still needed to determine the appropriate agricultural input use level to achieve efficiency. This study aims to assess the efficiency of paddy farming in Deli Serdang Regency, North Sumatra, Indonesia. This study evaluated the efficiency of paddy farming with three types: technical efficiency, allocative efficiency, and economic efficiency. A survey was conducted with 40 paddy farmers to obtain data on paddy production and agricultural input use such as seed, fertilizer, chemicals, and labor. Data envelopment analysis with an input approach was employed to analyze the data. The scores of technical efficiency, allocative efficiency, and economic efficiency were 0.935, 0.711, and 0.668, respectively. This study indicated that paddy farming in Deli Serdang Regency, North Sumatra, Indonesia, was technically efficient. However, it was allocative and economically inefficient. The unachieved cost minimization was the driving factor of the allocative inefficiency. Furthermore, this study also found that the condition of paddy farming increased the return to scale (IRS). This condition implied that the paddy farmers could escalate the paddy production and achieve efficiency by improving agricultural input use. Moreover, eco-friendly agricultural input is encouraged to minimize costs to improve allocative efficiency and support sustainable agriculture. Also, the government should take some actions and policies to improve the efficiency of paddy farming in Deli Serdang.